Streamlining Hospital Administration: Optimizing the Patient Queue System - Tobing, Vieri Kennedy Burju Lumban; Jazuli, A Muhamad (Jurnal Kewirausahaan dan Inovasi, 2025)
Purpose – This study aims to assess the optimal performance of the administrative service system at Universitas Brawijaya Hospital by determining the appropriate number of service counters to improve waiting time efficiency and cost effectiveness. Design/Methodology/Approach – This study employs a quantitative approach using a queuing system analysis method. Patient arrival and service time data were collected through six days of direct observation during peak hours. The analysis was conducted using POM-QM software with the (M/M/C):(FCFS/∞/∞) queue model. The evaluation focused on queue performance indicators and queue costs to determine the optimal number of service counters. Findings – The results show that operating three service counters is the optimal baseline based on queue cost efficiency. Although adding a fourth counter significantly reduces waiting time, the improvement is not proportional to the increase in queue costs. Therefore, a dynamic adjustment strategy for the number of open counters is recommended to manage patient surges while maintaining a balance between service efficiency and cost efficiency. Originality/Value This study provides a quantitative queue-based evaluation of hospital administrative services using the M/M/C model, offering evidence-based insights into determining the optimal number of service counters. The findings contribute a practical approach for balancing service efficiency and operational costs, supporting more adaptive and responsive hospital service management.